Environmental sustainability and management (ES & EM) practices among Service Sector Institutions in Kathmandu, Nepal - Sindhu Karki; Pratik Karki; Prakat Karki (Discover Sustainability)
Abstract Environmental sustainability (ES) emerged in response to the felt negative consequences of overexploitation of the environment and natural resources. ES has gained momentum in recent decades in areas of social policy, means of production, development, economy and everyday individual behaviours. The drive towards ES has been firmly based in scientific research which has been dominated by Western developed countries. For a tiny developing country like Nepal, its overall contribution to global environmental pollution and degradation is minimal; however, it has been disproportionately negatively affected by global warming, pollution, etc. There is sparse research on the various measures or state of environmental sustainability standards, policies or behaviours in Nepal. In this quantitative cross-sectional study, five types of Service Sector Institutions (SSI) from Kathmandu, Nepal were studied for their environmental sustainability (ES) and environment management (EM) measures in place at their facilities. SSIs were chosen because they have the distinct characteristic of being directly involved with large sections of populations, and hence hold the potential to pioneer innovative and effective solutions towards fostering environmental sustainability. ES was defined in terms of three measures related to sustainable freshwater use, energy use and waste management. The measures for EM included organizational capacity building and attitudes towards ES. Data was collected directly from representatives of the SSIs through self-report interviews or forms. The 104 SSIs included 25 schools, 26 restaurants, 16 hotels/lodges, 18 banks and 17 health care organizations. Based on frequency distributions and ANOVA tests, it was found that the overall extent of ES and EM practices among the 102 SSIs was dismally low in Kathmandu, Nepal. As given in the figure, educational institutions performed significantly better across all five ES and EM measures indicating highest prevalence of sustainability measures and practices. Banks performed significantly worst across all categories compared to the four other SSIs, indicating least amount of efforts in ES and EM. All five measures of environmental sustainability (ES) and environmental management (EM) were also strongly positively correlated amongst each other. A huge amount of effort is still required to revamp the existing ES and EM policies and organizational norms in Nepal. Moreover, it remaining challenging to change people’s attitudes and behaviours in order to effect lasting positive changes in the future and conserve the local environment better. Graphical Abstract